Consumption of key food groups during the postpartum period in low-income, non-Hispanic black mothers. (1st October 2017) - Kay, Melissa C.; Wasser, Heather; Adair, Linda S.; Thompson, Amanda L.; Siega-Riz, Anna Maria; Suchindran, Chirayath M.; Bentley, Margaret E.
Abstract: The postpartum period can impact diet quality and subsequently place women at greater risk for overweight or obesity. This study examined consumption of key food groups during the first 2 years postpartum among low income, non-Hispanic black, first-time mothers. Data were from the Infant Care, Feeding and Risk of Obesity Study, a cohort of 217 mother–infant dyads, followed from 3 to 18 months postpartum, collected from 2003 to 2007. At each study visit (3, 6, 9, 12, and 18 months) 24-h dietary recalls were collected. Consumption levels were compared to those recommended from the 2010 Dietary Guidelines for Americans (DGAs) for each of the following food groups: fruits, vegetables, grains, whole grains, protein foods and dairy, as well as an estimated upper limit for sugar-sweetened beverage (SSB) consumption. At each time point, mothers met recommended intake levels for grains and protein foods only. In random-intercept logistic regression models, no demographic or household characteristics were associated with a likelihood of consuming recommended levels for any of the food groups according to the DGAs. Given the low intake of fruits, vegetables, whole grains and lean protein foods and high intake of SSBs and refined grains, interventions targeting women's diet during the postpartum period are warranted.